Collisionless shock acceleration in the corona of an inertial confinement fusion pellet with possible application to ion fast ignition - Boella, E. (Philos Trans A Math Phys Eng Sci, 2021)
Two-dimensional particle-in-cell simulations are used to explore collisionless shock acceleration in the corona plasma surrounding the compressed core of an inertial confinement fusion pellet. We show that an intense laser pulse interacting with the long scale-length plasma corona is able to launch a collisionless shock around the critical density. The nonlinear wave travels up-ramp through the plasma reflecting and accelerating the background ions. Our results suggest that protons with characteristics suitable for ion fast ignition may be achieved in this way. This article is part of a discussion meeting issue ‘Prospects for high gain inertial fusion energy (part 2)’.